Combining axiomatic design and designed experiments for cellular manufacturing systems design framework. (13th November 2008) - Hachicha, Wafik; Masmoudi, Faouzi; Haddar, Mohamed
Cellular Manufacturing (CM) system has been recognised as an efficient and effective way to improve productivity in a factory. In recent years, there have been continuous research efforts to study different facet of CM system. They are developed to satisfy only one or limited Functional Requirements (FRs) of the CM system design. The literature does not contain much published research on CM design which includes all design aspects. In this paper we provide a framework for the complete CM system design. It combines Axiomatic Design (AD) and Experimental Design (ED) to generate several feasible and potentially profitable designs. The AD approach is used as the basis for establishing a systematic CM systems design structure. ED has been a very useful tool to design and analyse complicated industrial design problems. AD helps secure valid input-factors to the ED. An element of the proposed framework is demonstrated through a numerical example for a cell formation problem with alternative process.